ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA GUNA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA KELAS VI SD - Aji Budiarso (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2022)
This activity is the beginning of efforts to develop learning media to provide a significant increase in motivation and success in learning grade VI mathematics in three elementary schools of Gajah Mada Sarwas Cluster 1, Pemalang District. For the method itself, it uses descriptive qualitative with several research tools, namely observation, interviews, questionnaires, the last one is document analysis from various assessments. Then the techniques used in data analysis include data reduction, data presentation, and conclusion making. Based on the results of the initial study, it can be seen that student motivation in learning and student learning outcomes in mathematics lessons are very low. The average class only reaches 68. The lack of facilities and infrastructure, inadequate learning environment conditions, and low support from parents are some of the causes of the lack of optimal application of learning media that can be said to be in accordance with the situation of students in general. This research activity can be a data on the initial needs of developing learning media in schools so that class VI students are more motivated in participating in teaching and learning activities at school so that learning outcomes are included in the good category.